2015
DOI: 10.1016/j.diii.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Ablative therapies: Advantages and disadvantages of radiofrequency, cryotherapy, microwave and electroporation methods, or how to choose the right method for an individual patient?

Abstract: Several ablation techniques are currently available. Except for electroporation, all of these methods cause fatal damage at a cellular level and irreversible architectural deconstruction at a tissue level by thermal effects. Ablation of a tumor using one of these techniques, whether thermal or otherwise, requires applicators to be positioned from which the energy is delivered in situ. Some techniques, however, require several applicators to be inserted (multibipolar radiofrequency, cryotherapy and electroporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 15 publications
0
50
0
Order By: Relevance
“…Systematic characterisation of tissue ablation over a range of MW power and ablation time combinations was performed in ex vivo bovine liver, the most common tissue in which ablation laboratory trials are performed and reported [10]. This consisted of a grid of six time points (3,5,10,15,20, and 30 min) and six power settings (20,40,60,80, 100 and 130 W), providing the most used parameter combinations in the clinical practice. A total of 108 ablations were performed with three repetitions per power/time group, each on a piece of ex vivo bovine liver measuring at least 5 Â 10 Â 10 cm 3 .…”
Section: Phase I: Characterisation In Ex Vivo Bovine Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic characterisation of tissue ablation over a range of MW power and ablation time combinations was performed in ex vivo bovine liver, the most common tissue in which ablation laboratory trials are performed and reported [10]. This consisted of a grid of six time points (3,5,10,15,20, and 30 min) and six power settings (20,40,60,80, 100 and 130 W), providing the most used parameter combinations in the clinical practice. A total of 108 ablations were performed with three repetitions per power/time group, each on a piece of ex vivo bovine liver measuring at least 5 Â 10 Â 10 cm 3 .…”
Section: Phase I: Characterisation In Ex Vivo Bovine Livermentioning
confidence: 99%
“…Percutaneous thermal tumour ablation is now being commonly used for the treatment of focal tumours in the liver, lung, kidney, and bone [1][2][3][4][5]. Much of the initial literature, early basic research, and long-term clinical studies have been performed with radiofrequency (RF) energy-based systems [1].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite progress in RF devices (3)(4)(5)(6), the prognosis of cirrhotic patients with HCC treated by RF ablation as first-line is still impaired by local tumor progression (LTP) occurring within 2 years after RF ablation (7).…”
mentioning
confidence: 99%
“…For example, preoperative embolization may be performed to control intraoperative bleeding from hypervascular lesions such as metastases from renal or thyroid cancer. Focal ablative therapies, including cryoablation, radiofrequency ablation, and microwave ablation, lead to cellular necrosis and architectural tissue destruction by thermal effects on tumor cells [2426]. Although often associated with lower morbidity compared to extensive open surgery, these therapies can cause complications related to thermal damage of surrounding tissues, including skin necrosis [27, 28].…”
Section: Discussionmentioning
confidence: 99%